The Cost of Binge Drinking - Marco Francesconi; Jonathan James (Institute for the Study of Labor (IZA), 2015)
We estimate the effect of binge drinking on accident and emergency attendances, road accidents, arrests, and the number of police officers on duty using a variety of unique data from Britain and a two-sample minimum distance estimation procedure. Our estimates, which reveal sizeable effects of bingeing on all outcomes, are then used to monetize the short-term externalities of binge drinking. We find that these externalities are on average 4.9 billion per year (7 billion), about 80 for each man, woman, and child living in the UK. The price that internalizes this externality is equivalent to an additional 9p per alcoholic unit, implying a 20% increase with respect to the current average price.
Keywords: I12; I18; K42; 330; alcohol; health; road accidents; arrests; externalities